Juvenile Offenders: Reasons and Characteristics of Criminal Behavior - Dubovych, Olesia V. (2022)
The article examines the phenomenon of “juvenile delinquency”, assesses its actual state and establishes the tendencies of its manifestations. Juvenile delinquency in Ukraine as a part of crime in a broad sense arises and develops under the influence of certain determinants. The study of the causes and conditions of juvenile delinquency remains relevant today, which indicates the special danger of this kind of crime for the development of society. The purpose of the article is to study the state of the problem in Ukraine and the experience of other countries in minimising the criminal behaviour of minors in the process of property and non-property relations. The leading approach that was used when writing the article is the comparison and analysis of modern materials on the problems of criminal behaviour of criminals who have not reached the age of majority. As a result, it was possible to identify the social characteristics of juvenile criminals and the reasons for their criminal behaviour. Considerable attention is paid to the factors influencing the commission of crimes: a dysfunctional family, shortcomings of the educational process, the problem of alcohol and drug use by minors. In addition, some directions for the prevention of juvenile delinquency were developed. The applied value is the ability to change legislation in terms of work and correction of minor criminals’ behaviour